2018
DOI: 10.2147/ott.s162045
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of DJ-1 correlates with aggressive clinicopathological characteristics and poor prognosis in malignant tumors: a meta-analysis

Abstract: PurposeA number of studies have investigated the role of DJ-1 in the development and progression of malignant tumors. This meta-analysis aims to systematically estimate the rela-tionship between the expression level of DJ-1 and the malignant biological behaviors of tumors and to assess the clinical significances of DJ-1 in the prognosis and diagnosis of cancer.Materials and methodsWe searched PubMed, Web of Science, China National Knowledge Infrastructure and Wanfang databases from inception to December 1, 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…[22,23] The metaanalysis involved fourteen studies including 1,947 cancer patients and revealed that DJ-1 was an important biomarker in tumor evaluation and outcome. [24] The findings of our study provided that involvement in cyclin D1 and DJ-1, and in all the studied stages of PC compared to BPH. In addition, we found a significant association with the extent, the intensity, and overexpression of cyclin D1 and DJ-1 in PC, and BPH patients suggesting that they could be used as biomarkers for early detection of PC.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…[22,23] The metaanalysis involved fourteen studies including 1,947 cancer patients and revealed that DJ-1 was an important biomarker in tumor evaluation and outcome. [24] The findings of our study provided that involvement in cyclin D1 and DJ-1, and in all the studied stages of PC compared to BPH. In addition, we found a significant association with the extent, the intensity, and overexpression of cyclin D1 and DJ-1 in PC, and BPH patients suggesting that they could be used as biomarkers for early detection of PC.…”
Section: Discussionsupporting
confidence: 50%
“…[17,26,27] On the other hand, this association was not proved in many earlier studies. [9,14,16,24,28] Sensible explanations were suggested to prove that these differences are sample size, technical varieties of biopsy taking, staining type (cytoplasmic vs nuclear) and scoring system.…”
Section: Discussionmentioning
confidence: 99%